Pandemic 2019 - a harsh reality and its impact on the vulnerable - Jehan, Talat; Termizi, Mazbah (2022)
ABSTRACT In case of any emergency or calamity, there are a few segments and groups of our society who are considered vulnerable, marginalized, and neglected in terms of hardships and inequality. Even though as a pandemic COVID-19 treated everyone equally without any sort of discrimination such as marginalized population working in a non-formal industry or women-home based workers, women in post-war zones or conflict-affected areas, rural women, women and child migrants and ethnic minorities are more likely to suffer the most from limited movements and drastic decrease in their incomes (daily wagers, laborers for instance). The same is the case with COVID-19 and its continuous repercussions on human lives especially women, the elderly, differently-abled/PWDs, and children. This pandemic which is also referred to as a shadow pandemic limits and even stops economic growth and opportunities for many in different areas of life. This is the harsh reality one should admit that our health and overall system was not ready to deal with such threat which has multiple effects on the living beings and hence the non-agile response to the same risks the well-being of many. Considering the economic, emotional, societal, and psychological impact of the pandemic and the restrictions imposed, as a result, it was also observed that cases such as GBV or VAW were increased, as one in three women worldwide experience physical or sexual violence by someone they are close to or their partners. Since the outbreak of COVID-19, data and reports indicate that all types of violence against women and girls, particularly domestic violence, have increased and overall numbers of the affectees soared. The Covid-19 pandemic has also revealed the extent of exclusion that the most marginalized communities have experienced. But with threats and weaknesses, there are always opportunities that can be translated and served with the prospect of helping those who need us most.